Gambaran Tingkat Pengetahuan Tentang Diet Gizi Seimbang Pada Remaja di SMP Negeri 11 Medan Tahun 2022 - Yuliawati Anggraini Siregar; Rahma Agustia; Adelia Rahma; Sabila Tamimi Putri; Zhafira Kurnia Anwar (Jipmor: Jurnal Ilmu Pendidikan Dan Humaniora, 2024)
Abstract: Adolescence is a time of physical, emotional, and mental changes, and is an important period for maintaining behavior, including food intake. There are still many teenagers who only want a slim body rather than a healthy body. They also don’t really pay attention to health factors when choosing what to eat. Given the high nutritional problems that occur in adolescents, especially in schools, nutrition education that can raise the level of knowledge of children so as to prevent nutritional problems such as obesity and stunting in children. This study aims to describe the level of knowledge of SMP Negeri 11 Medan students about a balanced and nutritious diet. The type of this research is descriptive research using a cross-sectional research design. The subjects of this study were 30 students of SMP Negeri 11 Medan and it chosen by random sampling technique. The data were collected through pre-test and post-test questionnaires in a question format consisting of 10 multiple choice questions. The statistical test used univariate analysis to calculate the mean and percentage of each variable, such as gender, age, and level of knowledge of SMP Negeri 11 Medan students. The results of this study found that there was a change in the in the level of knowledge of SMP Negeri 11 Medan students before and after counseling. Therefore, balanced nutrition counseling is needed to increase knowledge and is expected to prevent various nutritional problems by changing adolescent health behavior.